Correlation of design parameters of lattice structure for highly tunable passive vibration isolator. (April 2023) - Azmi, Muhamad Syafwan; Ismail, Rainah; Putra, Azma
The purpose of this study is to correlate the influence of multiple size-based design parameters of lattice structure, namely, the unit cell (UC) and strut diameter (SD) through the static and dynamics analyses for passive vibration isolation application. The lattice structures were prepared by utilizing the fused deposition modeling (FDM) additive manufacturing (AM). The samples were designed to retain lattice structure's unique advantages while also conserving material consumption to fulfill the energy and cost demand. Through the static test, the crush behavior, failure mechanism, and mechanical properties were determined. The stiffness of lattice structure exhibited an increasing relationship with the unit cell and strut diameter where smaller unit cell and bigger strut diameter produced higher strength, and with that, higher load can be sustained. Through the dynamic vibration transmissibility test, it was found that the dynamic vibration results follow closely the trend in the static analysis. Lattice structure with larger unit cell and smaller strut diameter showed larger effective isolation region due to lower natural frequency value. The trade-off limit between stiffness for a lower natural frequency of the proposed design parameters was determined from the two parts analyses. The results suggest that most lattice isolators from the pool of design parameter combinations in this study have sufficient strength to withstand the predefined mass load and provide the most region for vibration isolation. The two proposed design parameters can later be used for a major or minor tuning of lattice isolators for other specific applications.